Enhanced 3-epi-25-hydroxyvitamin D3 signal leads to overestimation of its concentration and amplifies interference in 25-hydroxyvitamin D LC-MS/MS assays. (May 2014) - Flynn, N; Lam, F; Dawnay, A
Background: 3-epi-25-hydroxyvitamin D3 (3-epi-25OHD3 ) interferes in most liquid chromatography-tandem mass spectrometry (LC-MS/MS) assays for 25-hydroxyvitamin D (25OHD). The clinical significance of this is unclear, with concentrations from undetectable to 230 nmol/L reported. Many studies have quantified 3-epi-25OHD3 based on 25OHD3 calibrators or other indirect methods, and we speculated that this contributes to the observed variability in reported 3-epi-25OHD3 concentrations. Methods: We compared continuous MS/MS infusions of 3-epi-25OHD3 and 25OHD3 solutions, spiked both analytes into the same serum matrix and analysed patient samples to assess the effect of three different quantitation methods on 3-epi-25OHD3 concentration. Experiments were performed on an LC-MS/MS system using a phenyl column which does not resolve 3-epi-25OHD3, and a modified method utilizing a Zorbax SB-CN column that chromatographically resolves 3-epi-25OHD3 from 25OHD3 . Results: A greater 3-epi-25OHD3 signal, compared with 25OHD3, was observed during equimolar post-column continuous infusion of analyte solutions, and following analysis of a serum pool spiked with both analytes. 3-epi-25OHD3 signal enhancement was dependent on mobile phase composition. Compared with 3-epi-25OHD3 calibrators, indirect quantitation methods resulted in up to 10 times as many samples having 3-epi-25OHD3 concentrations ≥ 10 nmol/L, and an approximately fourfold increase in the maximum observed 3-epi-25OHD3 concentration to 95 nmol/L. Conclusions: Enhanced 3-epi-25OHD3 signal leads to overestimation of its concentrations in the indirect quantitation methods used in many previous studies. The enhanced signal may contribute to greater interference in some 25OHD LC-MS/MS assays than others. We highlight that equimolar responses cannot be assumed in LC-MS/MS systems, even if two molecules are structurally similar.